Retinal and choroidal blood flow variations after an endurance exercise: A real-life pilot study at the Paris Marathon - Mauget-Faÿsse, M.; Arej, N.; Paternoster, M.; Zuber, K.; Derrien, S.; Thevenin, S.; Alonso, A.-S.; Salviat, F.; Lafolie, J.; Vasseur, V. (Journal of Science and Medicine in Sport, 2021)
Objectives: To collect information about the retinal blood flow variations and other choroidal and retinal parameters during a prolonged effort such as marathon running. Design: Non-randomized prospective cohort study. Methods: Patients were recruited through an information campaign at the Rothschild Foundation Hospital (Paris, France). A first visit (V1) was planned in the month before the marathon. All participants underwent blood pressure measurement, fundus photography, spectral domain-optical coherence tomography (SD-OCT) and OCT-angiography (OCT-A). A second visit (V2) was scheduled within one hour of crossing the finish line. The same tests were repeated, using the same equipment. Results: Of the 31 runners who were included, 29 finished the marathon and attended V2. At baseline, various ophthalmological abnormalities were found in 45.2% of the 58 eyes, among which almost a third concerned the optic nerve and a quarter the pachychoroid spectrum. A significant decrease in retinal vascular plexus density was found between V1 and V2 (p < 0.01). While median macular and retinal nerve fiber layer (RNFL) thicknesses significantly increased after the marathon (p < 0.01), median choroidal thickness significantly decreased (p < 0.01). Both systolic and diastolic blood pressures significantly decreased (p < 0.01 and p = 0.021 respectively). Conclusions: Prolonged physical effort impacts the structure and vascularization of the retina and the choroid. Hypoxia and dehydration due to such an effort may induce a low ocular blood flow rate resulting in a choroidal thinning, contrasting with a transient subclinical ischemic edema of the inner retina and optic nerve head.